Cefoperazone induces esterase B expression by EstR and esterase B enhances cefoperazone activity at the periplasm - Neal Toewiwat; Wirongrong Whangsuk; Poonsakdi Ploypradith; Skorn Mongkolsuk; Suvit Loprasert (Elsevier, 2020)
The occurrence of antibiotic resistance bacteria has become a major threat to public health. We have recently discovered a transcriptional activator that belongs to MarR family, EstR, and an esterase B (EstB) with a newly proposed de-arenethiolase activity from Sphingobium sp. SM42. De-arenethiolase activity involves the removal of the small aromatic side chain of cephalosporin antibiotics as an excellent leaving group by the enzymatic CS bond cleavage. Here, we report the regulation of estB through EstR as an activator in response to a third generation cephalosporin, cefoperazone, antibiotic. Cefoperazone induced the expression of estB in wild type Sphingobium sp., but not in the estR knockout strain, and the induction was restored in the complemented strain. Moreover, we revealed the importance of EstB localization in periplasm. Since EsB has the ability to inactivate selected β-lactam antibiotics in vitro, it is possible that the enzyme works at the periplasmic space of Gram negative bacteria similar to β-lactamases. EstB was genetically engineered by incorporating NlpA binding motif, or OmpA signal sequence, or SpyTag-SpyCatcher to the estB gene to mobilize it to different compartments of periplasm; inner membrane, outer membrane, and periplasmic space, respectively. Surprisingly, we found that Sphingobium sp. SM42 and E. coli expressing EstB at the periplasm were more sensitive to cefoperazone. The possible drug enhancement mechanism by enzyme was proposed. This work might lead to a novel strategy to tackle antibiotic resistance problem.